Inclusion of people with disabilities, their needs and participation, into disaster management: a comparative perspective. (2nd January 2016) - Ha, Kyoo-Man
ABSTRACT: In the field of disaster management, not many have considered the role and needs of people with disabilities despite their number and condition. The purpose of this paper is to push for specific inclusion of people with disabilities, their needs and participation, into disaster management by studying relevant cases from Indonesia, Korea, and the USA. Qualitative content analysis was used as a major methodology by comparing three factors identified in these nations: government policies, schools and advocacy groups' efforts, and families and local communities' awareness. Three models, one from each country, were considered major takeaways from this study: the Indonesian moral inclusion, the Korean medical treatment without exclusion, and the US' extending social inclusion. In addressing the needs and participation of people with disabilities in disaster management, the following recommendations are put forward: for Indonesia, a move away from olden beliefs and misconceptions on disability (e.g. as a punishment) is imperative. In Korea, relevant fundamental laws (e.g. the Basic Act on Emergency and Safety Management) need to be revised while also studying advanced laws on the subject. For the USA, though the country is already advanced, overall improvement is still needed in terms of association with international non-governmental organizations, increase in the number of (emergency or disaster) response officials, and provision of better medical treatment.